Sağlık Profesyonellerinin Pelvik Taban Kas Egzersizlerini Uygulama ve Öğretme Konusundaki Bilgi Tutum ve Davranışlarının Değerlendirilmesi. - MAMUK, Rojin; DİŞSİZ, Melike; DİNÇ, Hüsniye (Journal of Academic Research in Nursing (JAREN), 2018)
Objective: This study was planned to assess the knowledge, attitudes and behaviors of healthcare professionals in relation to applying and teaching pelvic floor muscle exercises. Methods: The study conducted as a descriptive, cross-sectional study was carried out at five centers including four public hospitals and one private hospital. The sample of the study consisted of 304 healthcare professionals including doctors, nurses and midwives who volunteered to participate in the study. Data were collected by using the face-to-face interview method with the questionnaire forms prepared by the researchers in accordance with the literature. The data obtained were evaluated by using SPSS 20.0 package program on the computer. Number, percentage, arithmetic mean, chi-square significance test were used in the evaluation of the data. Results: The mean age of the participants was 31.86±7.61 years (min;17-max;61), and 23% (n=70) of the participants were physicians, 50% (n=155) were nurses and 26% (n=79) were midwives. It was determined that 56.6% of the healthcare professionals who participated in the study had a complete knowledge about PFME and most of them (68.1%) gain this knowledge from the training at school. When the groups were compared, it was found out that the significantly lower number of nurses had information about pelvic floor muscle exercises when compared with the other two groups (X2=15.824, p=0.000). Almost all of the participants stated that it was necessary to provide education on pelvic floor muscle exercises to all women starting from the adolescent period, and 61.9% of them expressed that they applied pelvic floor muscle exercises at least once in their lives. Conclusion: In conclusion, it was determined that the knowledge, attitudes and behaviors of healthcare professionals in relation to pelvic floor muscle exercises were not at the desired level and it is considered that it must be improved.